The Antecedents of Online Travel Satisfaction and Loyalty (Literature Review) - Rajesh Prettypal Singh; Wanda Gema P.A. Hidayat (Dinasti Publisher, 2026)
The objective of this research is to examine the existing literature on theories that affect customer e-satisfaction and e-loyalty in travel products. It seeks to explore the literature on the theoretical basis of factors influencing customers’ e-satisfaction and e-loyalty, both in general and specifically in the travel industry. Additionally, it proposes potential areas for further research on online travel satisfaction and loyalty. The study develops a conceptual framework by studying the theoretical background and literature research to identify the factors influencing e-satisfaction and customer e-loyalty. These factors include ease of use, information quality, privacy & security, and trust.The study reveals factors that influence e-customer satisfaction and e-customer loyalty in the travel and tourism industry. These factors include ease of use, information quality, privacy & security, and trust.The study proposes a conceptual framework that identifies the characteristics influencing e-customer satisfaction and e-customer loyalty. By actualizing real data, researchers can empirically test relationships among the factors in this framework.